2015
DOI: 10.3390/nu7031841
|View full text |Cite
|
Sign up to set email alerts
|

Food Group and Micronutrient Intake Adequacy among Children, Adults and Elderly Women in Greece

Abstract: The aim of the present study was to record the percentage of children, adults and elderly women in Greece meeting food and micronutrient intake recommendations. Additionally, the present study was aiming to identify the main food contributors of micronutrient intakes and assess the degree up to which meeting food intake recommendations also ensures micronutrient intake adequacy. Dietary intake data from three studies conducted in Greece (on 9–13-year-old children; 40–60-year-old adults; and 50–75-year-old wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 28 publications
2
33
1
1
Order By: Relevance
“…The important role of dairy in ensuring nutrient intake adequacy and sufficient concentrations of nutrient status blood indices was recently reported for the population of schoolchildren examined in the present study [2,6]. These recent findings showed that dairy consumption contributes to 63.2% of dietary calcium intake and 28.1% of total dietary zinc intake, as well as to 47.2%, 42.9% and 17.3% of the total dietary intakes of vitamin B 12 , B 2 and B 6 respectively [2].…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…The important role of dairy in ensuring nutrient intake adequacy and sufficient concentrations of nutrient status blood indices was recently reported for the population of schoolchildren examined in the present study [2,6]. These recent findings showed that dairy consumption contributes to 63.2% of dietary calcium intake and 28.1% of total dietary zinc intake, as well as to 47.2%, 42.9% and 17.3% of the total dietary intakes of vitamin B 12 , B 2 and B 6 respectively [2].…”
Section: Introductionmentioning
confidence: 65%
“…Milk and other dairy products (cheese and yogurt) are natural, rich sources of a wide range of essential nutrients [1,2]. In addition to their high protein content, daily consumption of dairy products contributes considerably to the overall diet quality and to the dietary intake adequacy of both vitamins (i.e., vitamins B 2 and B 12 ) and minerals (i.e., calcium, zinc, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations